Targeting PCSK9 for hypercholesterolemia - Norata, Giuseppe; Tibolla, G.; Catapano, A. (2014)
Dyslipidemias are a predominant risk factor for cardiovascular disease. Biological and genetic research has led to the identification of several genes and proteins that may be pharmacologically targeted to improve lipoprotein profiles and possibly cardiovascular outcomes in patients with dyslipidemia. The observation that proprotein convertase subtilisin/kexin type 9 (PCSK9) regulates the levels of circulating low-density lipoprotein C (LDL-C) by enhancing the degradation of the hepatic low-density lipoprotein receptor (LDLR) prompted the search for drugs that inhibit PCSK9 activity. Several approaches to inhibiting PCSK9 activity have been proposed; these involve inhibitory antibodies, small molecules, and gene silencing. To date, the most promising and advanced approach relates to monoclonal antibodies, which can decrease LDL cholesterol by 65-70%, even as an add-on therapy to a maximal dose of a statin. Phase III studies and large, event-driven clinical trials are ongoing and will fully address the viability and role of these drugs in clinical practice. © 2014 by Annual Reviews.